Contextual factors on physical demands in professional women`s soccer: Female Athletes in Motion study - Vescovi, J. D.; Falenchuk, O. (European Journal of Sport Science, 2019)
The aim of this study was to examine the impact of contextual factors on relative locomotor and metabolic power distances during professional female soccer matches. Twenty-eight players (forwards, n = 4; midfielders, n = 12; defenders, n = 12) that competed in a 90-min home and away match (regular season only). The generalised estimating equations (GEE) was used to evaluate relative locomotor and metabolic power distances for three contextual factors: location (home vs. away), type of turf (natural vs. artificial), and match outcome (win, loss and draw). No differences were observed for home vs. away matches. Moderate-intensity running (20.0 ± 1.0 m min-1 and 16.4 ± 0.9 m min-1), high-intensity running (8.6 ± 0.4 m min-1 and 7.3 ± 0.4 m min-1) and high-metabolic power (16.3 ± 0.5 m min-1 and 14.4 ± 0.5 m min-1) distances were elevated on artificial turf compared to natural grass, respectively. Relative sprint distance was greater during losses compared with draws (4.3 ± 0.4 m min-1 and 3.4 ± 0.3 m min-1). Overall physical demands of professional women`s soccer were not impacted by match location. However, the elevation of moderate and high-intensity demands while playing on artificial turf may have implications on match preparations as well as recovery strategies.